Deposition of Iridium Thin Films on Three‐Dimensional Structures With PE‐MOCVD. Issue 1 (2nd January 2015) - Yeh, Chia‐Pin; Lisker, Marco; Bläsing, Jürgen; Khorkhordin, Oleksandr; Kalkofen, Bodo; Burte, Edmund P.
Abstract : Iridium thin films are deposited on sub‐micrometer three‐dimensional trench structures by plasma‐enhanced metal‐organic chemical vapor deposition (PE‐MOCVD). The iridium precursor used in this study is (ethylcyclopentadienyl)(1, 5‐cyclooctadiene)iridium [Ir (EtCp)(1, 5‐COD)]. Various process conditions at substrate temperatures from 300 °C to 450 °C, with and without plasma enhancement, are investigated and compared. Crystal structure of the deposited iridium films is analyzed by X‐ray diffraction (XRD). Step coverage of the deposited iridium films on three‐dimensional trench structures is analyzed by scanning electron microscopy (SEM). Surface morphology is quantitatively evaluated by atomic force microscopy (AFM) and the electrical resistivity of the deposited Ir films is measured by the four‐point probe method. Abstract : Iridium thin films are deposited by PE‐MOCVD and are compared with the results of conventional MOCVD. The Ir films are deposited on 3D structures in order to evaluate their application as electrodes of 3D ferroelectric capacitors of FeRAM. The PE‐MOCVD technology shows advantages for Ir thin film deposition from the point of view of Ir thin film morphology, fill‐in, and step coverage on 3D structures. The top‐left SEM shows deposition by conventional MOCVD, and the other three SEMs by PE‐MOCVD. Plasma enhancement shows improvement of film profile and quality.